We Admire Modern Parents. The École des Parents du Québec and the Postwar Québec Family, 1940-1949 - Baillargeon, Denyse (Cultures of Citizenship in Post-War Canada, 1940-1955, 2003)
Keywords: Famille

Le Collège André-Grasset : 75 ans d'histoire - Bannon, Jacques (Fides, 2003)
Keywords: Collège André-Grasset; Collèges classiques; Communautés religieuses; Sulpiciens; Étudiants

H.-A. Verreau, ptre (1828-1901). Deuxième président de la Société historique de Montréal (suite*) - Beaudoin, Léo (Montréal en tête, 2003)
issued: 2003-24-00
Keywords: Chauveau; Pierre-Joseph-Olivier; Communautés religieuses; Histoire; Historiens; Société historique de Montréal; École normale Jacques-Cartier; Écoles normales

La formation académique des étudiants de premier cycle en psychologie à l'Université de Montréal: aspects situationnels, contextuels et globaux - Cagiotti, Isabelle (Université de Montréal, 2003)
Keywords: Psychologie; Université de Montréal; Étudiants

XIXe et XXe siècles: l’enseignement supérieur au Québec - Charland, Jean-Pierre (Cap-aux-Diamants, 2003)
issued: 2003-24-00
Keywords: Collèges classiques; Cégep; Université de Montréal

Growing Up in Three Languages: Triliteracy Practices of Chinese Immigrant Children in Quebec - Curdt-Christiansen, Xiao Lan (Université McGill, 2003)
Keywords: Chinois; Langue

Entre l’enseignement religieux et l’enseignement moral. Le régime d'option et le pluralisme religieux dans les écoles secondaires de la Commission des écoles catholiques de Montréal, 1983-1998 - David, Jocelyn (Université de Sherbrooke, 2003)
Keywords: Commission des écoles catholiques de Montréal

Duncan McEachran 1841-1924 / Duncan McEachran 1841-1924 - Fulleringer, Pat (Héritage Dorval, 2003)
Number: 1
Keywords: McEachran; Duncan McNab; Université McGill; École de médecine vétérinaire

Une histoire de l'éducation et du syndicalisme enseignant au Québec: essai - Graveline, Pierre (Typo, 2003)
Keywords: Enseignants; Grèves

Between the Future and the Present: Montreal University Student Youth and the Post-War Years, 1945-1960 - Hébert, Karine (Cultures of Citizenship in Post-War Canada, 1940-1955, 2003)
Keywords: Université McGill; Université de Montréal; Étudiants

Les diplômés de la Faculté de droit de l'Université de Montréal depuis 125 ans - Hétu, Jean (Éditions Thémis, 2003)
Keywords: Avocats; Droit; Université de Montréal

A Sixty-Year Evolution of Biochemistry at McGill University - Johstone, Rose (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Chimie; Université McGill

De Sainte-Croix à Maisonneuve : 75 ans d'histoire - Lachance, Laurent (Fides, 2003)
Keywords: Collèges classiques; Communautés religieuses; Congrégation de Sainte-Croix; Étudiants

Les Sœurs Grises à l’Université de Montréal, 1923-1947: de la gestion hospitalière à l’enseignement supérieur en nursing - Lamontagne, Esther; Cohen, Yolande (Revue d'histoire de l'éducation / Historical Studies in Education, 2003)
issued: 2003-23-00
Keywords: Communautés religieuses; Infirmières; Soeurs Grises; Université de Montréal

SAINT-JEAN, IDOLA - Lavigne, Marie; Stanton-Jean, Michèle (Dictionnaire biographique du Canada, 2003)

Louis-Philippe Audet: éducateur et chercheur - Lefebvre, Bernard (Lidec, 2003)
Keywords: Communautés religieuses; Enseignants; Frères des écoles chrétiennes; Histoire

Dans le mouvement étudiant à McGill - Lévesque, Andrée (Madeleine Parent, militante, 2003)
Keywords: Mouvement étudiant; Parent; Madeleine; Université McGill; Étudiants

Des enfants sous surveillance. La rééducation des jeunes délinquants au Québec (1840-1950) - Ménard, Sylvie (VLB, 2003)
Keywords: Délinquance; Enfants; Mont-Saint-Antoine

Le Rapport Parent et l’enseignement de l’histoire nationale au Québec entre 1960-1970: autopsie d’une réforme avortée - Moreau, Daniel (Université du Québec à Montréal, 2003)

Intersecting Discourses: Deaf Institutions and Communities in Montreal, 1850-1920 - Perreault, Stéphane- D (Université McGill, 2003)
Keywords: Clercs de Saint-Viateur; Communautés religieuses; Institution des sourdes-muettes; Institution des sourds-muets; Soeurs de la Providence; Sourds

"Unless She Gives Better Satisfaction”: Teachers, Protestant Education, and Community in Rural Quebec, Lochaber and Gore District, 1863-1945 - Poutanen, Mary Anne (Revue d'histoire de l'éducation / Historical Studies in Education, 2003)
issued: 2003-23-00

La formation universitaire et l'établissement d'une nouvelle profession: l'orthophonie-audiologie à l'Université de Montréal, 1956-1976 - Prud'Homme, Julien (Revue d'histoire de l'Amérique française, 2003)
issued: 2003-24-00
Keywords: Hôpitaux; Université de Montréal

Attracting Foreign Students: The Case of Two Universities in Québec - Racine, Nicolas; Villeneuve, Paul Y.; Thériault, Marius (Journal of Studies in International Education, 2003)
A number of factors may influence the recruitment of foreign students by universities, especially economic criteria pertaining to profitability. This article examines the cases of two Québec universities. Both feature teaching exclusively in French, a minority language in North America. Based on existing literature, hypotheses concerning the impact of language and international networking on the recruitment of foreign students are tested. Analysis reveals that even if regular use of French is important for recruitment, it is not the only variable involved. The geographical and social context of each university also plays an important role, as does the networking activities of academics who build relationships based on cooperation with foreign institutions.
Number: 3
Keywords: Université de Montréal; Étudiants

La relation entre les agents d'éducation scolaire et les agents d'éducation muséale dans le cadre d'une collaboration entre le musée et l'école - Vadeboncoeur, Guy (Université du Québec à Montréal, 2003)
Keywords: Musées